Peningkatan Kompetensi Sumber Daya Manusia Berbasis KSA melalui Penguatan Pengetahuan Matematika pada Siswa/i SMK Mathla’ul Anwar Kabupaten Tangerang - Vivi Iswanti Nursyirwan; Nina Valentika; Muhammad Sopiyana; Luh Nadi; Hamidah Hunein (Abdimisi, 2021)
We have conducted PKM in the odd semester of 2021/2022 at SMK Mathla'ul Anwar Sukadiri, Jalan Raya Mauk Km. 16 district. Sukadiri District. Tangerang, Buaran Jati, Kec. Sukadiri, Kab. Tangerang Prov. Banten. The theme of this PKM activity is "Improving the Competency of KSA-Based Human Resources through Strengthening Mathematics Knowledge for Students at SMK Mathla'ul Anwar, Tangerang Regency". In this PKM activity, the main focus is to provide socialization to SMK students about how to love mathematics, so that it can motivate SMK students to continue to develop knowledge and make students personally competent in their fields. Through this activity, it is hoped that students will find it easy to get a job, and it will be easy for them to continue their education in higher education. By studying mathematics, students are trained to be able to think logically, critically, creatively and structure in the end through this ability students can develop their mindset, especially in problem-solving. The implementation of community service is organized by the Accounting and Mathematics Study Program from Pamulang University in collaboration with lecturers and students in the Faculty of Economics and Business, Accounting Study Program and Mathematics Study Program and supported by the LPPM Pamulang University. Implementation of PKM Lecturers of the economics and business faculty of Pamulang University provides an experience that can improve students' cognitive aspects by 50% related to basic mathematics and there has been an increase in student motivation in learning mathematics.